Personality characteristics, defense styles, borderline symptoms, and non-suicidal self-injury in first-episode major depressive disorder - Peng, Bo; Liao, Jiwu; Li, Yang; Jia, Guangbo; Yang, Jihui; Wu, Zhiwei; Zhang, Jian; Yang, Yingjia; Luo, Xinxin; Wang, Yao; Zhang, Yingli; Pan, Jiyang (Frontiers in psychology, 2023)
Non-suicidal self-injury (NSSI) is commonly seen in adolescents with depression and is a high-risk factor leading to suicide. The psychological mechanisms underlying depression with NSSI are still unclear. The purpose of this study was to explore the differences in personality traits, defensive styles, and borderline symptoms among first-episode youth patients with depression and self-injury compared with patients with depression without self-injury and healthy populations. The current study recruited 188 participants, including 64 patients with depression and NSSI, 60 patients with depression without NSSI, and 64 healthy control subjects. Eysenck Personality Questionnaire, the Defense Style Questionnaire, the short version of the Borderline Symptom List, the Beck Depression Inventory, and the Ottawa Self-Injury Inventory were used to assess all participants. Patients with depression and NSSI showed more psychoticism than patients with depression without NSSI and healthy control subjects. Patients with depression and NSSI presented more intermediate defense styles than healthy control subjects. In the patients with depression and NSSI group, the frequency of self-injury in the last week was negatively correlated with mature defense styles and positively correlated with depressive symptoms and borderline symptoms. Further regression analysis showed that EPQ-psychoticism and depressive symptoms were independent risk factors for NSSI in patients with depression. This study found that patients with depression and self-injury presented more neuroticism, introversion, EPQ-psychoticism, immature defenses, intermediate defenses, and borderline symptoms. Self-injury frequency was negatively correlated with mature defense styles and positively correlated with depressive symptoms and borderline symptoms. EPQ-Psychoticism and depressive symptoms are risk factors for predicting non-suicidal self-injury in patients with depression.